ANALISIS PENGEMBANGAN MODEL BISNIS KANVAS PERUSAHAAN HORTIKULTURA PT. XYZ - Muhamad Zulkyfli Luthan; Ratna Winandi; Amzul Rifin (Forum Agribisnis, 2019)
PT XYZ is one of agribusiness companies which offers horticultural products in Indonesia which are considered as eco-profit and low-pesticide-based-products. The purpose of this research is to describe and improve the business model of PT XYZ based on the Business Model Canvas (BMC) approach and SWOT analysis then the analysis is carried out the preparation of a new business model prototype for PT XYZ. This study utilizes structured interviews assisted with questionnaire instruments as data collection procedures and both Business Model Canvas (BMC) approach and identification of SWOT as research methodology. The results of the SWOT analysis on nine elements of Business Model Canvas (BMC) show that there are internal and external factors that become strengths and weaknesses for the company in carrying out its business model and also what opportunities and threats from external factors affect PT XYZ's business processes are. The SWOT identification results then used as background to formulate a new business improvement model. Improvement of PT XYZ's business model is aims to streamline production in satisfying the demand of Horeca (Hotel, Restaurant, Catering) customers. In supporting expansion of PT XYZ by having effective and efficient business model, the improvements that need to be done are escalating production management, doing production forecast, creating and socializing SOPs to farmers as the main partner, enhancing offline promotion by joining events held by Horeca (Hotel, Restaurant, Catering) events and dividing customer segment into three segments by sorting them based on priority which are Horeca (Hotel, Restaurant, Catering) as the first market segment, modern markets as the second market segment, and traditional market as the third market segment.